2015
DOI: 10.1002/ange.201412110
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Ligand Cooperative Pathway for Intermolecular Oxa‐Michael Additions to Unsaturated Nitriles

Abstract: An unprecedented catalytic pathway for oxa-Michael addition reactions of alcohols to unsaturated nitriles has been revealed using aPNN pincer ruthenium catalyst with adearomatized pyridine backbone.The isolation of acatalytically competent Ru-dieneamido complex from the reaction between the Ru catalyst and pentenenitrile in combination with DFT calculations supports amechanism in which activation of the nitrile through metal-ligand cooperativity is akey step.The nitrile-derived Ru-N moiety is sufficiently Brøn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…[13] Theresulting complex (4), showing methylation of the carbon atom linking the phosphine and NHC moieties, was isolated as am ixture of two diastereomers (ratio 6:1) differing by the position of the methyl group with respect to the iodine atom (Scheme 2, middle). [14,15] These results clearly indicated that the deprotonation of 2 occurs at the CH 2 bridge forming as ufficiently nucleophilic carbon species to react with electrophiles such as MeI or CO 2 . In asecond experiment, the deprotonated species was exposed to CO 2 (1 atm) affording the complex 5 in 89 % yield (Scheme 2, bottom), whose solid state structure highlights the existence of atripodal NHC-phosphine-carboxylate scaffold with af acial arrangement of the carbonyl ligands ( Figure 1d).…”
supporting
confidence: 64%
“…[13] Theresulting complex (4), showing methylation of the carbon atom linking the phosphine and NHC moieties, was isolated as am ixture of two diastereomers (ratio 6:1) differing by the position of the methyl group with respect to the iodine atom (Scheme 2, middle). [14,15] These results clearly indicated that the deprotonation of 2 occurs at the CH 2 bridge forming as ufficiently nucleophilic carbon species to react with electrophiles such as MeI or CO 2 . In asecond experiment, the deprotonated species was exposed to CO 2 (1 atm) affording the complex 5 in 89 % yield (Scheme 2, bottom), whose solid state structure highlights the existence of atripodal NHC-phosphine-carboxylate scaffold with af acial arrangement of the carbonyl ligands ( Figure 1d).…”
supporting
confidence: 64%
“…In asecond experiment, the deprotonated species was exposed to CO 2 (1 atm) affording the complex 5 in 89 % yield (Scheme 2, bottom), whose solid state structure highlights the existence of atripodal NHC-phosphine-carboxylate scaffold with af acial arrangement of the carbonyl ligands ( Figure 1d). [14,15] These results clearly indicated that the deprotonation of 2 occurs at the CH 2 bridge forming as ufficiently nucleophilic carbon species to react with electrophiles such as MeI or CO 2 .…”
mentioning
confidence: 87%
“…The activation of CO 2 involving C-nucleophilic actor ligands has attracted increased attention and was recently reviewed by Song and co-workers . In this regard, the role of MLC-triggered activation/binding of CO 2 was discussed for various complexes. Recent studies also concern the MLC-triggered activation of multiple bonds such as carbonyls and CN-multiple bonds in complexes with pyridine-based pincer ligands. Against this background, we herein report the extension of the substrate scope to S=O bonds, as complex 1 readily reacts with the adduct of 1,4-diazabicyclo[2.2.2]­octane and sulfur dioxide (DABSO), which is a convenient source of SO 2 , to give the sulfinate compound fac- K­[Re­( amidopy-OSO )­(CO) 3 ] ( 2ab ) under Re–O and C–S bond formation (Scheme , 2ab ).…”
mentioning
confidence: 99%